FTIR and FT Raman Spectra, Vibrational Assignment and Analysis of 1,2-Cyclohexanedione - Mani, P.; Suresh, S. (Asian Journal of Chemistry, 2010)
FTIR and FT Raman spectra of 1,2-cyclohexanedione have been recorded in the regions 4000- 200 and 4000-30 cm-1, respectively. The vibrational analysis has been carried out by assuming Cs symmetry. The observed frequencies were assigned to various modes of vibrations on the basis of intensity, frequencies from allied molecules and the normal coordinate calculations. The potential energy distributions associated with normal modes are also reported. The assignment of fundamental vibrational frequencies for 1,2-cyclohexanedione agree well with calculated frequencies.